1987
DOI: 10.1007/bf00349929
|View full text |Cite
|
Sign up to set email alerts
|

The use of computed tomography to quantitate bone formation after distraction epiphysiolosis in the rabbit

Abstract: A study of limb lengthening by distraction epiphysiolysis in the rabbit tibia is presented. For this purpose a special external distraction device was developed, which allowed 10 mm lengthening of the leg. Bone formation in the distraction zone was quantified by means of computed tomography. Cross-sectional scan planes at 1.5 mm separation revealed bone formation proceeding for several weeks after the end of the distraction period. A period of bone remodeling followed, resulting in the formation of a solid cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
3

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 4 publications
0
7
0
3
Order By: Relevance
“…Chances of observing an effect from an added external stimulus might be highest as early in the distraction phase as possible. Van Roermund et al (35) reported that in this rabbit tibia elongation model, active net bone formation occurred from the start of the distraction until 3-4 weeks after reaching maximal elongation.…”
Section: Discussionmentioning
confidence: 78%
“…Chances of observing an effect from an added external stimulus might be highest as early in the distraction phase as possible. Van Roermund et al (35) reported that in this rabbit tibia elongation model, active net bone formation occurred from the start of the distraction until 3-4 weeks after reaching maximal elongation.…”
Section: Discussionmentioning
confidence: 78%
“…1,13,17,19,39 Therefore, the original hypothesis in the current study could not be proved. It seems that calcitonin cannot accelerate maturation of regenerate bone, at least under the conditions and standards of the current experiment and as far as DEXA is able to appreciate such an effect.…”
Section: Discussionmentioning
confidence: 85%
“…The current model along with the relative technical parameters (operative technique, waiting period, and rate and speed of lengthening) were based on the literature and the authors' pilot studies. [17][18][19]23,39 …”
mentioning
confidence: 99%
“…Moreover, these characteristics appear to be long-standing, in contrast to lengthening in which the newly formed bone tends to assume characteristics similar to that of the contralateral bone [1][2][3]. In particular, in bone transport the regenerated osseous segments consistently presented a cortical thickness and density that were less than that of the contralateral segment, with an enlargement of the medullary canal (Figs.…”
Section: Discussionmentioning
confidence: 99%